2012
DOI: 10.1155/2012/104565
|View full text |Cite
|
Sign up to set email alerts
|

Application of Bioactive Coatings Based on Chitosan for Soybean Seed Protection

Abstract: Soybean seeds suffer attacks of various pests that result in a decreased yield in northeastern China. Until recently, people use pesticides such as insecticides to achieve the goal of controlling pests. Chitosan extracted from deacetylation of chitin is promising candidates as a seed-coating agent to control agrotis ypsilon, soybean pod borer, and soybean aphid effectively. An experimental study on influences of chitosan with different concentrations on pest controlling and soybean growth was made in the paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 16 publications
9
47
1
4
Order By: Relevance
“…In our study, chitosan (up to 2%) and snail shell (up to 2%) seed coating increased the percentage of germination compared to control. These results confirm the earlier findings that seeds soaked with chitosan increased the germination percentage (Zeng et al, 2012). This could be due to the excellent film-forming capacity of chitosan, making it easy to form a semi-permeable film on the seed surface which can maintain the seed moist and absorb the moisture from the soil.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, chitosan (up to 2%) and snail shell (up to 2%) seed coating increased the percentage of germination compared to control. These results confirm the earlier findings that seeds soaked with chitosan increased the germination percentage (Zeng et al, 2012). This could be due to the excellent film-forming capacity of chitosan, making it easy to form a semi-permeable film on the seed surface which can maintain the seed moist and absorb the moisture from the soil.…”
Section: Discussionsupporting
confidence: 91%
“…Distilled water was sprinkled on the trays every two days to avoid dryness. Germination was confirmed by a shooting of the radicule and the germination rate evaluated as in Zeng et al (2012 …”
Section: Evaluation Of Germination Ratementioning
confidence: 99%
“…Chitosan is derived from chitin by the deacetylation of the N-acetyl group using hot alkaline sodium hydroxide (Muzzarelli, 1973;Pillai, Paul, & Sharma, 2009). Chitosan is used as a plant growth enhancer as well as to prevent disease attack on seeds (Zeng, Luo, & Tu, 2012). It has been reported that foliar application of chitosan results in lesser transpiration thus reducing the application of water in agriculture (Valenta, Christen, & Bernkop-Schnürch, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…This biopolymer is a large cationic polysaccharide mainly obtained from waste materials from seafood processing (Guan et al, 2009), with antiviral, antibacterial, and antifungal properties (El-Hadrami et al, 2010). When CH is applied to plant seeds, their germination index is enhanced, the mean germination time is reduced, shoot height, root length, and seedling vigor are increased (Bhaskara Reddy et al, 1999;Ruan and Xue, 2002;Shao et al, 2005;Guan et al, 2009;Kananont et al, 2010;Ziani et al, 2010;Zeng et al, 2012), vegetative growth is increased, time to flowering is reduced (Ohta et al, 1999), and fresh weight is increased (Asghari-Zakaria et al, 2009). CH has been applied not only to seeds but also to seedlings.…”
Section: Introductionmentioning
confidence: 99%